Management of radicular cysts in patients with a history of systemic disease: Penatalaksanaan kista radikular pada pasien dengan riwayat penyakit sistemik - Abul Fauzi; Yossy Yoanita Ariestiana; Yeyen Sutasmi (Makassar Dental Journal, 2024)
Radicular cysts are the most common type of odontogenic cysts and are of inflammatory origin. Treatment of the cysts can be by enucleation or by marsupialisation, with a good treatment prognosis. This article is intended to illustrate the management of odontogenic cysts in a patient with a history of systemic disease. A 56-year-old man presented with a complaint of wanting to remove a residual root in the maxillary frontal region although there had never been any complaints about the tooth. Radiogra-phic examination revealed extensive bone destruction in the region, with a working diagnosis of radicular cyst. After history ta-king, it was found that the patient had a history of hypertension and diabetes. The management of patients with odontogenic cysts, especially radicular, is enucleation. The management of dental cysts in patients with systemic diseases needs to be specialised.